Kepemimpinan Digital, Manajemen Inovasi dan Daya Saing di Era Revolusi Industri 4.0: Peran Mediasi dari Quality Management - Abdi Fadhlan; Tonny Yuwanda; Sitti Rizki Mulyani (Jurnal Bisnis dan Kewirausahaan, 2022)
The Industrial Revolution 4.0 is a new challenge for several industries where industry players are forced to improve their systems and services in order to compete. The purpose of this study is to see the effect of digital leadership, innovation management on competitive advantage with quality management as a mediating variable. The population of this research is 70 employees, by using the Slovin formula  a sample of 60 respondents was obtained from Samsung Center Padang with data collection using questionnaires. Structural Equation Model (SEM) – Partial Least Square (PLS) was used to analyze the data in this study. The results of this study are: 1) Digital leadership and innovation management have a positive and significant impact on competitive advantage. 2) Digital leadership and innovation management have a positive and significant impact on quality management. 3) Quality management has a significant positive effect on the competitive advantage of Samsung Center Padang. 4) Quality Management mediates Digital leadership and innovation management towards competitive advantage.